Celiac Disease in Women with Hip Fractures - LeBoff, Meryl S. (2013)
OBJECTIVE: Celiac disease is associated with decreased bone density, however, the risk of fractures in celiac disease patients is unclear. We compared the prevalence of celiac disease between a group of women with hip fractures and a group of women undergoing elective joint replacement surgery and the association between celiac disease and vitamin D levels. METHODS: Two hundred eight community dwelling and postmenopausal women were recruited from Boston, MA (n=81) and Baltimore, MD (n=127). We measured tissue transglutaminase IgA by ELISA to diagnose celiac disease and 25-hydroxyvitamin D (25(OH)D) levels by radioimmunoassay in both women with hip fractures (n=157) and the control group (n=51), all of whom were from Boston. Subjects were excluded if they took any medications or had medical conditions that might affect bone. RESULTS: Median serum 25(OH)D levels were significantly lower (p< 0.0001) in the hip fracture cohorts compared to the elective joint replacement cohort (14.1 ng/ml vs. 21.3 ng/ml, respectively). There were no differences in the percentage of subjects with a positive tissue transglutaminase in the women with hip fractures versus the control group (1.91% vs. 1.61%, respectively). CONCLUSION: Vitamin D levels are markedly reduced in women with hip fractures, however hip fracture patients did not show a higher percentage of positive tissue transglutaminase levels compared with controls. These data suggest that routine testing for celiac disease among hip fracture patients may not prove useful, although larger prospective studies among hip fracture subjects are needed.